91 Differentiating Physiological Left Ventricular Hypertrophy from Hypertrophic Cardiomyopathy in Athletes: Proposed Echocardiographic Protocol. (31st May 2014) - Malhotra, Aneil; Sheikh, Nabeel; Dhutia, Harshil; Siva, Arun; Millar, Lynne; Merghani, Ahmed; Narain, Rajay; Dores, Helder; Sharma, Sanjay; Papadakis, Michael
Abstract : Purpose: Hypertrophic cardiomyopathy (HCM) is the commonest cause of SCD in young athletes. The differentiation between physiological left ventricular hypertrophy (LVH) and morphologically mild hypertrophic cardiomyopathy (HCM) is crucial and an erroneous diagnosis has potentially serious consequences. Day to day clinical practice most commonly utilises transthoracic echocardiography (ECHO) for this purpose. The British Society of Echocardiography (BSE) recently produced a diagnostic algorithm to facilitate the differentiation between these two morphologically similar, yet clinically distinct entities. This study aimed to validate the recommended echocardiographic parameters. Methods: A cohort of 56 competitive athletes with LVH (maximal wall thickness >12 mm) was evaluated. Of these, 19 were athletes with physiological LVH while 37 were diagnosed with HCM based on the results of comprehensive evaluation including cardiac MRI, familial evaluation and gene testing. The ECHO data were analysed for 4 parameters: 1) S', average of septal and lateral walls (cm/s): >9 LVH vs <9 HCM; 2) E/A: >1 LVH vs <1 HCM; 3) E', average of septal and lateral walls (cm/s): >9 LVH vs <9 HCM; 4) E/E': <12 LVH vs >12 HCM. Results: Athletes with physiological LVH were younger (24.7 vs 29.1 years, p = 0.03) and exhibited a lower maximum left ventricular wall thickness (13.2 vs 16.4 mm, p = 0.05) compared to the athletes with HCM. All 37 athletes with HCM were male whereas the cohort of physiological LVH comprised of 17 males and 2 females. A summary of the sensitivity, specificity, positive (PPV) and negative (NPV) predictive values of individual parameters to identify athletes with HCM is presented in Table 1. Table 1 showing the sensitivity, specificity, PPV and NPV of the respective echo parameters. Conclusion: The current BSE guidelines are informative in helping differentiate physiological LVH from HCM in athletes to some extent. However, their sensitivity in identifying athletes with HCM is poor. Prior knowledge of patient demographics, clinical history and additional investigations should be taken into consideration to aid the interpretation of the echo data.